2019
DOI: 10.5603/arm.2019.0023
|View full text |Cite
|
Sign up to set email alerts
|

Levels of CD4+ CD25+ T Regulatory Cells in Bronchial Mucosa and Peripheral Blood of Chronic Obstructive Pulmonary Disease Indicate Involvement of Autoimmunity Mechanisms

Abstract: Introduction: Many theories have been proposed to explain pathogenesis of COPD; however, remains unclear why the majority of smokers (~80%) do not develop COPD, or only develop a mild disease. To explore if COPD has an autoimmune component, the role of T regulatory lymphocytes (Tregs) in the lung tissue of COPD patients is of crucial importance. Material and methods: Bronchial tissue biopsy samples were prospectively collected from 64 patients (39 COPD and 25 controls-15 smokers and 10 non-smokers). The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Previous studies have demonstrated a decreased level of IL-10 in the serum of COPD stage III patients compared to patients with disease stages I and II [ 16 ] and to those with disease stages II and III, who also presented lower frequencies and numbers of Foxp3 mRNA transcripts compared with non-obstructed smokers [ 17 ]. Sileikiene et al (2019) evaluated the expression of Treg cells in bronchial tissue biopsies and in the blood of COPD patients [ 28 ]. The authors demonstrated decreases in the number of Treg cells in the bronchial epithelium and peripheral blood of severe/very severe COPD patients compared to those of patients with mild/moderate COPD and healthy smokers, suggesting that severe COPD is diagnosed in patients with lower levels of Tregs in the blood and respiratory tract, which corroborates our findings [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a decreased level of IL-10 in the serum of COPD stage III patients compared to patients with disease stages I and II [ 16 ] and to those with disease stages II and III, who also presented lower frequencies and numbers of Foxp3 mRNA transcripts compared with non-obstructed smokers [ 17 ]. Sileikiene et al (2019) evaluated the expression of Treg cells in bronchial tissue biopsies and in the blood of COPD patients [ 28 ]. The authors demonstrated decreases in the number of Treg cells in the bronchial epithelium and peripheral blood of severe/very severe COPD patients compared to those of patients with mild/moderate COPD and healthy smokers, suggesting that severe COPD is diagnosed in patients with lower levels of Tregs in the blood and respiratory tract, which corroborates our findings [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sileikiene et al (2019) evaluated the expression of Treg cells in bronchial tissue biopsies and in the blood of COPD patients [ 28 ]. The authors demonstrated decreases in the number of Treg cells in the bronchial epithelium and peripheral blood of severe/very severe COPD patients compared to those of patients with mild/moderate COPD and healthy smokers, suggesting that severe COPD is diagnosed in patients with lower levels of Tregs in the blood and respiratory tract, which corroborates our findings [ 28 ]. These authors also noted that patients with mild/moderate COPD and healthy smokers exhibited a higher number of Treg cells than the never-smoker controls, which they considered consistent with a protective role of these cells in COPD development.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the anti-inflammatory process mediated by the Treg response, decreased numbers of Treg cells in the bronchial epithelium were reported in patients with severe and very severe COPD compared to those with mild and moderate COPD and healthy smokers ( 38 ). These results demonstrated that lower levels of Treg cells in the blood and lungs were observed only in severe COPD stages.…”
Section: Th17/treg In Clinical Studiesmentioning
confidence: 99%
“…However, PBMC samples were not obtained from the same subjects from which the lung tissue samples were collected ( 41 ). In fact, only a few studies have evaluated samples from lungs and peripheral blood obtained from the same patient ( 27 , 38 ), which can be a limiting factor when studying human samples. Table 1 summarizes the main findings regarding the Th17/Treg imbalance in clinical studies, divided by inflammatory marker and by systemic and local responses.…”
Section: Th17/treg In Clinical Studiesmentioning
confidence: 99%
“…Um estudo recente avaliou a expressão de células Treg em biópsias de tecido brônquico e no sangue de pacientes com DPOC. Os autores demonstraram diminuição das células Treg no epitélio brônquico de pacientes com DPOC grave e muito grave, em comparação aos com DPOC leve e moderada e fumantes saudáveis, sugerindo que a DPOC grave é diagnosticada em pacientes com níveis menores de células Treg no sangue e trato respiratório, corroborando com nossos achados(60).Ademais, o TGF-β é considerado como uma citocina chave na diferenciação de células TCD4+ em Th17 ou Treg. Foi demonstrado que o TGFβ induz a expressão de Foxp3 em células TCD4+ naive, convertendo-as em células Treg (61) e também que a IL-6 juntamente com TGF-β induz a diferenciação para Th17 e inibe a diferenciação de Treg induzida por TGF-β (62).Além da função imunomoduladora, o TGF-β tem atividade fibrogênica e seu aumento pode resultar em fibrose das vias aéreas e contribuir para a limitação do fluxo aéreo em doenças das pequenas vias aéreas, como a DPOC(63).…”
unclassified